Studi Pengaruh Adisi H2O Terhadap Konversi Alfa-Pinen Menjadi Terpineol Menggunakan Katalis H2SO4 - Nurmila, Mila; Julianto, Tatang Shabur; Rubiyanto, Dwiarso (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2014)
The study of addition H2O to the alpha-pinene conversion into terpineol using H2SO4 catalyst has been carried out. The conversion process carried out using a hydration reaction for 4 hours with the variation of the number of water. The mole ratio of alpha-pinene to water l:5, 1:10,1:15, 1:20,1:25. While the H2SO4 as catalyst concentration has equated to the concentration of alpha-pinene for all conditions. The mixture which are alpha-pinene, with varying amounts of water, sulfuric acid catalyst and a fixed cancentration equivalent to the concentration of alpha-pinene and acetone as media refluxed at a temperature of 80-85°C during 4 hours. Hydration products were analyzed using GC-MS ond GC instrument.The results showed that the ratio of alpha-pinene reaction conditions: water l:10, alpha pinene converting as much as 30,29% with selectivity terpineol products as much as 30,395%.